2004
DOI: 10.1097/01.ta.0000087646.68382.9a
|View full text |Cite
|
Sign up to set email alerts
|

Early Tracheostomy versus Prolonged Endotracheal Intubation in Severe Head Injury

Abstract: In severe head injury early tracheostomy decreases total days of mechanical ventilation or mechanical ventilation time after development of pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
167
1
19

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(193 citation statements)
references
References 33 publications
6
167
1
19
Order By: Relevance
“…Tracheostomy may reduce the incidence of VAP, the duration of MV, and the length of ICU stay (34,35). However, the optimal timing of tracheostomy is still undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Tracheostomy may reduce the incidence of VAP, the duration of MV, and the length of ICU stay (34,35). However, the optimal timing of tracheostomy is still undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Diferentes autores han encaminado sus esfuerzos a evaluar las posibles indicaciones y potenciales ventajas consecuentes a realizar precozmente la TRQ en pacientes con traumatismo craneoencefálico. Un número considerable de estudios en enfermos traumatológicos, con o sin TCE, encuentran que se acorta la duración de la VM y la estancia en UCI, aunque con conclusiones contradictorias en cuanto a la incidencia de neumonía y mortalidad [1][2][3][4]14,34 . Por el contrario, en otros trabajos clínicos llevados a cabo en pacientes similares no se demuestra ningún tipo de beneficio con la realización de TRQ precoz, puesto que no se acorta la duración de la estancia en UCI, ni se disminuyen los días de VM, ni se demuestra una menor incidencia de neumonía ni una disminución de la mortalidad 5,35 .…”
Section: -221unclassified
“…A prospective cohort study compared 31 subjects with isolated TBI who received a tracheostomy at d 5 or 6 versus 31 similar TBI subjects who did not undergo tracheostomy and found that tracheostomy was associated with decreased overall ventilator time, decreased ventilator days after diagnosis of VAP, and a shorter period to extubation, but no differences in rates of pneumonia or hospital mortality. 49 A retrospective cohort study compared 27 TBI subjects who received early tracheostomy (Ͻ 7 d of intubation) versus 28 TBI subjects with late tracheostomy (Ͼ 7 d of intubation) and found that early tracheostomy was associated with decreased ICU stay, but had no effect on hospital mortality, hospital stay, ventilator days, rates of VAP, or hospital cost. 65 A small retrospective study compared 11 TBI subjects with early tracheostomy (within 8 d) versus 17 subjects with late tracheostomy (after 8 d) and found a decrease in 28-d mortality, but no differences in ICU mortality, ICU-free days, or ventilator-free days.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%